Application of natural deep eutectic solvents to extract ferulic acid from Ligusticum chuanxiong Hort with microwave assistance. Issue 39 (23rd July 2019) - Xie, Yilin; Liu, Herui; Lin, Li; Zhao, Maojun; Zhang, Li; Zhang, Yunsong; Wu, Yichao
Abstract : In this study, natural deep eutectic solvents (NADES) combined with microwave-assistance extraction (MAE) were researched to establish an environmentally-friendly method for extracting ferulic acid from Ligusticum chuanxiong Hort. Abstract : In this study, a method using natural deep eutectic solvents (NADES) combined with microwave-assistance extraction (MAE) was researched for the first time to establish an environmentally-friendly method for extracting ferulic acid from Ligusticum chuanxiong Hort. 20 kinds of NADES were initially screened, then response surface methodology was performed to optimize the NADES-MAE extraction of ferulic acid in L. c on the basis of the results of single-factor experiments. The results demonstrated that NADES could provide better extraction yields of ferulic acid than conventional solvents, and the combination of choline chloride and 1, 2-propanediol was the most effective. The optimal conditions were an extraction time of 20 min, an extraction temperature of 68 °C, and a solvent-to-solid ratio of 30 : 1 mL g −1 . Under these conditions, the extraction yield of ferulic acid with NADES-MAE (2.32 mg g −1 ) was higher than that using traditional extraction methods. This research demonstrates that this approach, which adopts NADES as a green solvent and MAE as an assistant extraction technique, could be an excellent choice to design an environmentally-friendly method for extracting phenolic compounds in various materials.